Correlation between Beliefs on Translation and the Use of It as an English Learning Strategy - Humairoh, Mega Fariziah Nur; Agustina, Febrina Rizky (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2020)
This current study focuses its investigation on the correlation between students’ beliefs about the use of translation as an English learning strategy and the strategic use of translation in learning English by EFL students in Indonesia. This current study is aimed 1) to investigate the correlation between students’ beliefs and the use of translation as a learning strategy 2) to examine the developmental of the use of translation as a learning strategy across different year of study. One hundred seventeen undergraduate students, consisting 67 freshmen and 50 sophomores participated in this correlational study. The data were collected by frequency of an Indonesian Version of the Inventory for Beliefs about Translation for beliefs measurement and the Inventory for Translation as a Learning Strategy. Correlation and t-test were employed in the study. Correlation analysis reveals that a strong positive correlation between students’ beliefs about translation and their use of translation as learning strategy. T-test finds the significant difference in the use of translation as learning strategy between freshman and sophomore learner.